Gender perspective and autonomy of will: A harmonizing approach to the duty of judicial protection and women's right to freedom of decision and self-determination - Shwoihort, Sergio Juniors (2022)
This article addresses a specific situation in cases of violence against women with regards to judicial protection: How do we act when victim decides not to exercise her right to leave a life free of violence? This is a dull issue, and any position is fully debatable. This article seeks to analyze this issue to draw the lines that best meet the harmonization of the rights, powers and duties at stake.